К познанию фауны личинок трематод пресноводных моллюсков Крыма - Стенько, Р.П. (Вестник зоологии, 1976)
During four seasons of 1970-1973 8763 mollusks of 17 species from reservoirs, rivers and ponds of the Crimea were studied. Cercaria of 24 Trematoda species belonging to 15 genera from 12 families and metacercaria of 5 species are found in the mollusks. The Trematoda cercaria of birds predominate in the collections as to the quantity of species and occurrence (11 species). The greatest number of the Trematoda species is found in Radix auricularia (11 species) and Planorbis planorbis (8 species).